Implementasi Virtualisasi Proxmox Ve Mengatasi Keterbatasan Sistem Untuk Meningkatkan Efisiensi Layanan Metro Global News - Susilo, Zefanya Damar Aristo; Himamunanto, Agustinus Rudatyo; Lase, Kristian Juri Damai (STIKOM Tunas Bangsa Pematangsiantar, 2025)
Metro Global News is a media company that, to this day, remains dependent on third-party hosting services as a means to reach its users. This reliance has led to limitations in independently managing server infrastructure, reduced system flexibility, increased operational costs, and minimal control over service configurations. This study aims to implement an internal server infrastructure using virtualization technology based on Proxmox VE as a solution to these challenges. Tools such as Netdata and Portainer were utilized to monitor system performance and resource usage in real-time. The system was built using two virtual machines (VMs), each running separate services within containers, enabling modular management and supervision. Monitoring results through Netdata recorded a total of 4,211 active metrics covering performance indicators such as CPU, RAM, disk I/O, and network usage, with log consumption of only 552 KB at the highest tier. Meanwhile, Portainer reported 4 active containers running application services, 3 storage volumes, and 5 images, with a total RAM allocation of 4.1 GB and the use of 2 CPU cores. All services operated stably under full load conditions without downtime, indicating that the system can function optimally with minimal resources. These findings confirm that Proxmox VE is an effective and cost-efficient solution for building internal IT infrastructure, particularly for medium-scale organizations requiring full control over their systems. This study also opens opportunities for further development through features such as clustering and high availability to enhance service reliability in the future.